PROPOSED MARKETING STRATEGY FOR SUSTAINABLE GROWTH OF PERSIB OFFICIAL STORE - Wijaya Umar, Rendy
Indonesia is one of the countries with the most people, and it is also one of the countries that loves football the most. Indonesia's football market is very big, and football has become a big business there. PT Persib Bandung Bermatabat is in charge of the football club Persib Bandung, which is one of Indonesia's teams. The Persib Official Store, located at Graha Persib, 3rd floor, Jalan Sulanjana No. 17 Bandung, is managed and sold by PT. Persib Bandung. The Persib Official Store sells merchandise divided into three product categories: Fashion, Jersey, and Accessories. The issue that arises in this business is that sales fluctuate from January to June 2022. As a result, the purpose of this study is to learn about Persib Official Store's business situation and to recommend the best marketing strategy for increasing sales and becoming more competitive in the football merchandise industry's development. The author uses internal and external analysis to analyze the company's business situation when conducting this research. Marketing Mix 4Ps, Segmenting, Targeting, Positioning (STP), and VRIO analysis are part of internal analysis. The author conducted an online questionnaire survey of ten people in early September 2022. As a result, Persib Official Store's marketing was ineffective. In terms of products, Persib Official Store currently lacks intellectual property rights so that many competitors easily imitate and sell their products. In terms of price , Persib Official Store offers relatively high prices in the market, so competitors take advantage of this opportunity by imitating and selling at lower prices. In terms of place, Persib Official Store only has one offline store which is located at JL. Sulanjana and has limited parking space. They also have an official website for an online store. and sales through e-commerce channels such as Shopee, Tokopedia, Blibli, and Tiktok stores where customers can buy their wares. In terms of promotion, Persib Official Store currently lacks digital marketing personnel. Furthermore, the authors use Porter's five forces analysis, competitor analysis, and customer analysis for external analysis. The author also distributes online questionnaires that will be used to collect information from respondents in the context of conducting consumer research. The author uses quantitative research methods with a total of 209 respondents in his consumer analysis research. The authors use the Statistical Package for the Social Sciences (SPSS) to analyze the results of their consumer analysis research, which shows that there is a positive and significant influence of Brand Awareness, Advertising, and Sales Promotion variables on consumer purchase intentions. Based on internal and external analysis, the author uses SWOT analysis to see the company's business conditions which include Strengths, Weaknesses, Opportunities and Threats to the company, which is then continued using the TOWS matrix analysis and produces a new strategy for Persib Official Store. The new marketing strategy proposed by the author to Persib Official Store consists of Create Social Media Content Plan, Execute Social Media Campaigns, Maximize Customer Testimonials on Their Website, Add a Live Chat Feature on Their Website, Provide a Variety of Payment Methods on Their Website, Collaborate With The Community, Collaborate with Persib Players, Build a Second Offline Store, Make Bundle Packages and Discount Promotions, Have Digital Marketing Team, and Have Intellectual Property Rights.